ANALISIS TENTANG PERMOHONAN PEMBATALAN PERKAWINAN MENURUT AGAMA ISLAM BERDASARKAN UNDANG UNDANG NO 1 TAHUN 1974 TENTANG PERKAWINAN - Suwandi Arifin (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
Abstracts In the process the cancellation request in the religious marriage about calling, examination, and shall be made in accordance with the procedures of filling a divorce. The trial judge UDH examine the request for revocation of marriage no later than 30 (thirty) days after receipt of the latter/request, a decision which has obtained permanen legal force, the clarks are obliged to make a statement about the concellation of the marriage  anddressed to employees registrar for holding registration of marriage annulment.  Cancellation of marriage in article 28 paragraph (2) of low no. 1 of 1974 about the marriage states that the decision as not retroactive to : children who are born of the marriage. Husbands or wives who act ingood faith, except to the joint property, if the cancellation of marriage is based on the basis of another first marriage. The third person not included in (a) and (b) insofar as they acquire rights in good faith prior to the decision on the revocation has permanent legal force. Keywords : Annulment  Of Marriage According To The Religion Of Islam,  Marriage Law